Preliminary paleomagnetic study of Cretaceous dykes in SE-Tibet - Antolin, B; Appel, E; Dunkl, I; Ding, L; Montomoli, C; El Bay, R; Gloaguen, R (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1231 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.20